« J’en peux plus… j’arrête ». Les ressorts de la (dé)mobilisation professionnelle d’un DRH - Biaggi Chloé (La Nouvelle Revue du Travail)
HR Directors are occasionally forced to engage in adversarial interactions with company employees and their representatives, interactions that they may find emotionally taxing. Based on a study of the career path of a HR Director – crystallised in a sequence of episodes culminating in his departure from the company - this paper questions the conditions under which the individuals fulfilling such roles are more likely to remain committed to their work. “Careers” – construed in the interactionist sense of the concept - will be used to better understand the (dis)engagement processes that are in question here. The article also advocates theoretical de-fragmentation, being the idea that to understand the willingness to work of senior managers (and indeed, of frontline operatives), attention should be paid to the symbolic and material rewards of work without forgetting the practical conditions of its execution.